2016
DOI: 10.12688/f1000research.10104.1
|View full text |Cite
|
Sign up to set email alerts
|

Electroantennogram response of the parasitoid, Microplitis croceipes to host-related odors: The discrepancy between relative abundance and level of antennal responses to volatile compound

Abstract: Herbivores emit volatile organic compounds (VOCs) after feeding on plants. Parasitoids exploit these VOCs as odor cues to locate their hosts. In nature, host-related odors are emitted as blends of various compounds occurring in different proportions, and minor blend components can sometimes have profound effects on parasitoid responses. In a previous related study, we identified and quantified VOCs emitted by cotton plant-fed Heliothis virescens (Lepidoptera: Noctuidae) larvae, an herbivore host of the parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Interestingly, Morawo et al found that decanal elicited 0.82 mV EAG response in Microplitis croceipes, which was the highest response value. However, decanal accounts for only 1% of cotton-fed host volatiles [69].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Morawo et al found that decanal elicited 0.82 mV EAG response in Microplitis croceipes, which was the highest response value. However, decanal accounts for only 1% of cotton-fed host volatiles [69].…”
Section: Discussionmentioning
confidence: 99%
“…For comparisons between means, analysis of variance (ANOVA) was conducted, followed by the Tukey's HSD (honestly significant difference) test (significance level: P < 0.05). In EAG assay, data were calculated as absolute values by deducting the control (solvent) responses from treatment (component) responses . Student's t ‐test ( P < 0.05) was used to determine the differences in EAG values between males and females.…”
Section: Methodsmentioning
confidence: 99%
“…In EAG assay, data were calculated as absolute values by deducting the control (solvent) responses from treatment (component) responses. 32 Student's t-test (P < 0.05) was used to determine the differences in EAG values between males and females.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The signals can be assessed and analyzed with other software. 47 With the help of advanced data acquisition analysis systems, electroantennograms have been successfully employed to establish olfactory biosensors for a wide variety of odorant identifications. [35][36][37] For instance, using the antenna of the Colorado potato beetle, an electroantennographic detector was successfully used to detect volatile organic compounds emitted by its host plants, which could also be used to explore the plant-insect interactions.…”
Section: Insect-antenna-based Biosensors With Electroantennographymentioning
confidence: 99%